Antibiotic Combined with Epitope-Specific Monoclonal Antibody Cocktail Protects Mice Against Bacteremia and Acute Pneumonia from Methicillin-Resistant Staphylococcus aureus Infection - Duan L (Dove Medical Press, 2021)
LianLi Duan,1,* Jinyong Zhang,1,* Zhifu Chen,1 Qiang Gou,1 Qingshan Xiong,1 Yue Yuan,1 Haiming Jing,1 Jiang Zhu,2 Li Ni,3 Yuling Zheng,4 Zhiyong Liu,5 Xiaokai Zhang,1 Hao Zeng,1 Quanming Zou,1 Zhuo Zhao1 1National Engineering Research Center of Immunological Products, Department of Microbiology and Biochemical Pharmacy, College of Pharmacy, Army Medical University, Chongqing, 400038, People’s Republic of China; 2Department of Pathology, Southwest Hospital, Army Medical University, Chongqing, 400038, People’s Republic of China; 3Obstetrics and Gynecology, The First People’s Hospital of Jiulongpo District, Chongqing, 400050, People’s Republic of China; 4State Key Laboratory of Pathogens and Biosecurity, Institute of Microbiology and Epidemiology, Beijing, 100071, People’s Republic of China; 5Department of Laboratory Medicine, Southwest Hospital, Army Medical University, Chongqing, 400038, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhuo Zhao; Quanming Zou Email zhaozhuo198309@163.com; qmzou2007@163.comPurpose: We previously reported that monoclonal antibody (mAb) cocktail improves survival in Staphylococcus aureus infection. In this study, we used acute pneumonia model and lethal sepsis model to investigate the efficacy of antibiotic combined with epitope-specific mAb cocktail in treating MRSA252 infection.Methods: MRSA252 was challenged by tail vein injection or tracheal intubation to establish sepsis model or pneumonia model. One hour after infection, the mice received a single intravenous injection of normal saline, vancomycin, and vancomycin combined monoclonal antibody, linezolid alone or linezolid combined monoclonal antibody. Daily record survival rate (total 7 days), bacterial load, histology, cytokine analysis of serum and alveolar lavage fluid, and in vitro determination of the neutralizing ability of antibodies to SEB toxin and Hla toxin explained the mechanism of antibody action.Results: The mAb cocktail combined with low doses of vancomycin or linezolid improved survival rates in acute pneumonia model (70%, 80%) and lethal sepsis model (80%, 80%). Epitope-specific monoclonal antibodies reduced bacterial colonization in the kidneys and lungs of mice and inhibited the biological functions of the toxins Hla and SEB in vitro. Compared to the antibiotic alone or PBS groups, the combination group had higher levels of IL-1α, IL-1β and IFN-γ and lower levels of IL-6, IL-10, TNF-α. Further, the combination of antibiotic and mAb cocktail improved infection survival against the clinical MRSA isolates in a lethal sepsis model.Conclusion: This study demonstrates a novel method to treat people with low immunity against drug-resistant S. aureus infections.Keywords: methicillin-resistant Staphylococcus aureus, immunodominant epitope, monoclonal antibody, lethal sepsis, pneumonia